Lesson study in Brazil: a decade of academic productions on profession and teacher education - de Oliveira, Herlison Nunes (2021)
This article reports a survey of academic productions in Brazil about the Japanese Jugyo-Kenkyu methodology (Lesson Study), applied to the initial and continuing education of teachers in various parts of the world. For this purpose, Internet searches were conducted for works published between 2008 and 2018 with eight descriptors. The search, guided by the principles of Systematic Review, resulted in the selection of 49 publications from four regions: North, Northeast, Southeast and South. The analysis of this corpus indicates advances in research, still embryonic, with the Lesson Study in Brazil. It is believed that the volume of academic productions on Lesson Study will increase as the dissemination of its formative potential expands in Brazil.